2023
DOI: 10.3390/su15031964
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation for Immersive Virtual Reality Learning Environment: A Systematic Literature Review

Abstract: This systematic review broadly attempted to synthesize all relevant evidence residing in the Scopus, IEEE Xplore and MDPI databases, in order to inform the related Research Questions of this work. More precisely, the review protocol includes a broad and comprehensive search for eligible data sets from the Scopus, IEEE Xplore and MDPI databases, published from January 2017 to December 2022 by using inclusion/exclusion search criteria. Medical Education Research Study Quality Instrument (MERSQI) was commissioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The research found that a third of the studies (24%) focused on subjects within the realm of Natural Sciences, encompassing disciplines such as geography, biology, and chemistry. This was followed by Engineering (15%) ranked second highest, with the third highest VR content designs in Health Science (11%) (Cao et al, 2023). Figure 2 presents the imbalance in the development of VR learning content.…”
Section: Reasons For Not Adopting Vr Into Hrmmentioning
confidence: 98%
See 3 more Smart Citations
“…The research found that a third of the studies (24%) focused on subjects within the realm of Natural Sciences, encompassing disciplines such as geography, biology, and chemistry. This was followed by Engineering (15%) ranked second highest, with the third highest VR content designs in Health Science (11%) (Cao et al, 2023). Figure 2 presents the imbalance in the development of VR learning content.…”
Section: Reasons For Not Adopting Vr Into Hrmmentioning
confidence: 98%
“…Figure 2 presents the imbalance in the development of VR learning content. Source: (Cao et al, 2023) The research paper by Cao (2023) notes that the challenge of limited VR content has been raised by various researchers and continuous to hinge the adoption of VR within the educational field (Lege & Bonner, 2020); more specifically, within the human resources (HR) realm where VR can be used successfully for HR training purposes. The implication of not utilizing VR in HR management is that it may lead to a significant impact on an organization's operations, with processes not being automated, which can result in wasting cost and time.…”
Section: Reasons For Not Adopting Vr Into Hrmmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from recent reviews [21] and metanalyses [25,26] affirm that VR-based educational methodologies consistently outperform conventional instructional techniques in multiple aspects including knowledge acquisition, skill development, and motivational levels. These advantages are primarily attributed to the high levels of interactivity and the degree of immersion that VR platforms afford [27].…”
Section: Virtual Reality In Cultural Educationmentioning
confidence: 99%